2009
DOI: 10.1136/thx.2008.106286
|View full text |Cite
|
Sign up to set email alerts
|

Influenza but not pneumococcal vaccination protects against all-cause mortality in patients with COPD

Abstract: Background: Influenza and pneumococcal vaccination are recommended in patients with chronic obstructive pulmonary disease (COPD). A recent study from Tayside found a reduced risk of all-cause mortality with vaccination in patients with COPD. The Health Improvement Network (THIN) database was used to test this hypothesis in a different data source. Methods: The THIN database was searched for patients with COPD. Vaccination status against Pneumococcus and the annual influenza vaccination status were determined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
12

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 18 publications
0
49
0
12
Order By: Relevance
“…For example, rates of FV in patients over 60 years old went from <30% in 1995 to >70% in 2005, which resulted in a decrease in all-cause mortality. 25 An even greater increase in PV rate (from 0 to >70%) occurred over the same period of time; however, there was no discernible benefit for its use. Another study found that FV reduced exacerbations in chronic obstructive pulmonary disease, showing that the vaccine can influence patient care.…”
Section: Discussionmentioning
confidence: 99%
“…For example, rates of FV in patients over 60 years old went from <30% in 1995 to >70% in 2005, which resulted in a decrease in all-cause mortality. 25 An even greater increase in PV rate (from 0 to >70%) occurred over the same period of time; however, there was no discernible benefit for its use. Another study found that FV reduced exacerbations in chronic obstructive pulmonary disease, showing that the vaccine can influence patient care.…”
Section: Discussionmentioning
confidence: 99%
“…6,17,18 Diğer yandan, pnömokok aşısının KOAH'lı hastalarda pnömo-kokal pnömoni riskini azalttığı gösterilse de mortaliteyi etkilemediği belirlenmiştir. 19,20 Ancak pnömokok aşılama-sından sonra IgG ve IgG2 düzeylerinin anlamlı derecede yükselmesi, aşının koruyucu özelliğini kanıtlamaktadır. 21 Sonuçta KOAH olgularında aşı uygulamasının mortalite ve morbiditenin azaltılmasında etkin bir yaklaşım olduğu görülmektedir.…”
Section: Discussionunclassified
“…Skład szczepów w szczepionce jest każdego roku dobiera ny w ten sposób, aby uodparniać przeciw szczepowi spodziewanemu w następnym sezonie. Szczepienia przeciw grypie zmniejszają częstość zaostrzeń, hospitalizacji oraz śmiertelność u chorych na POChP [65].…”
Section: Szczepienia Przeciw Grypieunclassified